2013
DOI: 10.1080/22311866.2013.817741
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Analysis, Antimicrobial, Scavenging Ability and Cytotoxic Activity of Leaves ofSyzygium calophyllifoliumWalp

Abstract: The Syzygium calophyllifolium is a large evergreen tree growing in higher altitude in Southern Western Ghats, India. The ethyl acetate extract of leaves contain higher proportions of sesquiterpenoids and triterpenoid compounds that showed effective antimicrobial screening against some of bacterial and fungal strains. The extract showed maximum inhibition zones against Enterococcus faecalis and Trichophyton mentagrophytes. The extract also showed notable antioxidant activity and at higher concentration scavenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The volatile constituents found in this study corroborate the constituents that are commonly found in several plants of the Myrtaceae family and belonging to the Syzygium genus, such as Syzygium aromaticum (Raina et al, 2001), Guinea-Bissau (Noudogbessi et al, 2008), Syzygium densiflorum (Saranya et al, 2012), Syzygium calophyllifolium (Vignesh et al, 2013) and Syzygium benthamianum (Deepika et al, 2013).…”
supporting
confidence: 84%
“…The volatile constituents found in this study corroborate the constituents that are commonly found in several plants of the Myrtaceae family and belonging to the Syzygium genus, such as Syzygium aromaticum (Raina et al, 2001), Guinea-Bissau (Noudogbessi et al, 2008), Syzygium densiflorum (Saranya et al, 2012), Syzygium calophyllifolium (Vignesh et al, 2013) and Syzygium benthamianum (Deepika et al, 2013).…”
supporting
confidence: 84%
“…The extract also showed strong cytotoxicity and antioxidant activity. The major constituent was squalene assessed through GC‐MS analysis (Vignesh et al., 2013 ). S. cordatum fruit, bark, and wood extracts contained several triterpenoid compounds determined by TLC, IR, MS, CC.…”
Section: Phytochemical Constituentsmentioning
confidence: 99%
“…(E)‐2ʹ,4ʹ‐dihydroxy‐6ʹ‐methoxy‐3ʹ,5ʹ‐dimethylchalcone), assessed in HPLC method (A. H. Memon et al., 2015 ). Ethyl acetate extract of S. calophyllifolium leaves contained 60 compounds; among these, major compounds are γ‐eudesmol; β‐vatirenene; 4‐methoxy‐naphthalene‐1‐carboxylic acid; α‐gurjunene; eicosane; germacrene D, assessed through GC‐MS analysis (Vignesh et al., 2013 ). Methanol extract of fruits contained 12 compounds; among these, major compounds are 3‐piperidinamine; 1‐ethyl‐; N‐[3‐[n‐aziridyl]propylidene]‐3‐methylaminopropylamine; 1,3‐propanediamine; n′‐[3‐(dimethylamino)‐n–n‐dimethyl, determined through GC‐MS analysis (Sathyanarayanan et al., 2018 ).…”
Section: Phytochemical Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Syzygium densiflorum is a large canopy tree growing in high elevation evergreen forests between the altitudes 1500-2300 m. [2] Syzygium species are reported to exhibit anti-diabetic, [3] anti-fungal, [4,5] anti-inflammatory, [6] anti-bacterial, [5,7,8] anti-oxidant, [9] anti-hyperlipidemic [10] and growth inhibitory activity. [11] In recent years, research on natural anti-oxidants from plants is increased owing to their free radical scavenging potential.…”
Section: Introductionmentioning
confidence: 99%